BASIS DATA TERDISTRIBUSI UNTUK DATA INVENTARIS BARANG - Agustini, Eka Puji; Purnamasari, Susan Dian (Universitas Bina Darma, 2016)
Abstract: A system can not be separated from the database. The database can either be petrified management in data processing in a rapid, precise and accurate . One of distributed database is one of 3 types of databases that can be used apart from the type of relational database, database integration. For a company that has many branches of the need for a database that can hold large amounts of data with very necessary , a distributed database is appropriate for the management of data bases that can be used in several branches of the company. This research will discuss a distributed database system for managing data inventory. So the data inventory at each branch can be distributed and reported quickly and efficiently. Keywords: Basis data, Basis data terdistribusi, Inventaris